Gambaran Status Gizi Pada Ibu Usia Produktif di Desa Kranggan - Laras Eka Nur Hasanah; Afifah Istiqomah; Hilda Diniyati; Winda Sauci Panjaitan (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
Background: Gizi status is a measure of the balance between gizi asupan and bodily needs. Negative gizi status in infants, whether it be kelebihan or kekurangan, can increase the risk of PTM and reproductive health problems. The rising prevalence of obesity among Indonesian women indicates changes in eating habits and lifestyle, including in rural areas. Objectives: The purpose of this study is to understand the gizi status of the people in Desa Kranggan, Kabupaten Sampang. Methods: The study, which was conducted in July 2025, used a quantitative deskriptif design with cross-sectional data. The study's population consists of all 19–49-year-olds living in Desa Kranggan, with a sample size of at least 25 respondents using total sampling. The gizi status is determined using the Indeks Massa Tubuh (IMT), which is classified according to the Kementerian Kesehatan RI (2020) standard. Results: According to the study's findings, the majority of respondents had a higher gizi status, with 56.0% being overweight, 28.0% being obese, and 16.0% being normal. This indicates that the gizi's problems in Desa Kranggan are gradually the obesity. One contributing factor is the consumption of foods high in energy and fat, the level of physical activity, and the level of nutrition knowledge. Conclusions: The issue of nutrition has shifted from undernutrition to overnutrition, particularly in rural areas, leading to confusion and frustration among mothers. Interventions focused on nutrition education and promotion of physical activity are needed to prevent the rise in obesity and related diseases.